2020
DOI: 10.1139/cjz-2019-0191
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral phenotype does not predict habitat occupancy or angling capture of largemouth bass (Micropterus salmoides)

Abstract: Fish behavior types can predict angling vulnerability, providing insights about how recreational fishing may lead to artificial trait selection. Most vulnerability studies have focused on species with active foraging strategies, and the impact of environmental conditions on vulnerability has not been quantified. The objective of this study was to determine the influences of behavior types and habitat on angling vulnerability of largemouth bass (Micropterus salmoides (Lacepède, 1802)) — a sit-and-wait predator.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 68 publications
1
2
0
Order By: Relevance
“…In addition to differences in re-descension, we also found that bluegills and black crappies differed in behavior in arena-based trials at the surface. In our study, control black crappie spent more time in the center of the arena than slow-retrieved and vented bluegill, and tended to spend less time in the center of the arena than control bluegill, a metric that has been previously described as an indicator of stress or a general lack of behavioral boldness (Keiling et al, 2020;Pearish et al, 2019), which means that black crappie behavior in our study could indicate a greater degree of barotrauma-induced disturbance than bluegill. These results somewhat echo previous results in these species, which found differences in reflex-responsiveness between the species in surface trials (Althoff et al, 2021).…”
Section: Discussionsupporting
confidence: 58%
“…In addition to differences in re-descension, we also found that bluegills and black crappies differed in behavior in arena-based trials at the surface. In our study, control black crappie spent more time in the center of the arena than slow-retrieved and vented bluegill, and tended to spend less time in the center of the arena than control bluegill, a metric that has been previously described as an indicator of stress or a general lack of behavioral boldness (Keiling et al, 2020;Pearish et al, 2019), which means that black crappie behavior in our study could indicate a greater degree of barotrauma-induced disturbance than bluegill. These results somewhat echo previous results in these species, which found differences in reflex-responsiveness between the species in surface trials (Althoff et al, 2021).…”
Section: Discussionsupporting
confidence: 58%
“…Similarly, other studies with experimental angling have found a lack of relationship between boldness and boldness syndromes and capture method (Keiling et al, 2020;Kekäläinen et al, 2014. A recent study of angling vulnerability within experimental ponds with largemouth bass (Micropterus salmoides) did not find that boldness behavioral phenotype predicted angling capture (Keiling et al, 2020). However, they found that the angler, not the gear itself, caught fish with different behavioral phenotypes.…”
Section: Discussionmentioning
confidence: 88%
“…Even small differences in passive fishing techniques can alter targeting of different behavioral types within a population (Härkönen et al, 2016;Wilson et al, 2015). However, variation in experimental results across species and fishing techniques indicate that the link between behavioral type and vulnerability to harvesting is likely species and context-dependent (Diaz Pauli & Sih, 2017;Keiling et al, 2020;Wilson et al, 2011). Vulnerability to capture likely depends on a combination of a fish's internal state, their encounter rate with fishing gear, and that fishing gear's particular characteristics (Lennox et al, 2017).…”
mentioning
confidence: 99%